Determination of Sun Protective Factor of Selected Medicinal Plants from Western Nepal - Pradhan, Suman Prakash; Adhikari, Kapil; Nepal, Saroj; Pandey, Bishnu Prasad (Journal of Nepal Chemical Society, 2020)
Plant extracts contain active ingredients that can absorb, reflect or scatter the sunlight, depending on their nature. The effectiveness of plant extracts as a skin protective agent can be determined by measuring the sun protection factor (SPF). The main aim of this study was to investigate the potential of selected medicinal plant extracts as a component in sunscreen production in modern cosmetics. The absolute methanol extract of six medicinal plants namely; Asparagus racemosus, Bergenia pacumbis, Melia azedarach, Murraya koenigii, Pleurospermum benthamii, and Thymus linearis were examined in-vitro for their sun protective ability by ultraviolet-visible spectrophotometry method with the application of Mansur equation. Our results revealed that most of the plant extracts possess prodigious SPF values as compared with commercial sunscreen. The greatest SPF value was found in P. benthamii (34.97±0.25), T. linearis (24.98±0.60), and B. pacumbis (24.02±0.15). These results show that these plant extracts can act as a very good antisolar agent.